Sudan: The Impacts of COVID-19 on the Economy, Household Income, and Poverty - Raouf, Mariam (2020)
Mariam Raouf POLICY SEMINAR Virtual Event - COVID-19’s Short-term Impacts on Economies, Food Systems and Poverty in African and Asian Countries: Economywide Estimates from Economywide Models Co-Organized by IFPRI and the CGIAR Research Program on Policies, Institutions, and Markets (PIM) AUG 11, 2020 - 09:30 AM TO 10:45 AM EDT